2009
DOI: 10.1073/pnas.0908507106
|View full text |Cite
|
Sign up to set email alerts
|

Metalloproteinase MT5-MMP is an essential modulator of neuro-immune interactions in thermal pain stimulation

Abstract: Peripheral interactions between nociceptive fibers and mast cells contribute to inflammatory pain, but little is known about mechanisms mediating neuro-immune communication. Here we show that metalloproteinase MT5-MMP (MMP-24) is an essential mediator of peripheral thermal nociception and inflammatory hyperalgesia. We report that MT5-MMP is expressed by CGRP-containing peptidergic nociceptors in dorsal root ganglia and that Mmp24-deficient mice display enhanced sensitivity to noxious thermal stimuli under basa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
56
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(63 citation statements)
references
References 40 publications
6
56
1
Order By: Relevance
“…Early work highlighted its role in peripheral nervous system (PNS) neuroinflammation (Folgueras et al, 2009), and neuropathic pain after spinal cord lesion (Komori et al, 2004). More recently we demonstrated that MT5-MMP deficiency in the 5xFAD mouse model of AD remarkably ameliorated the outcome of the pathology affecting neocortical and hippocampal functions (Baranger et al, 2016b).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Early work highlighted its role in peripheral nervous system (PNS) neuroinflammation (Folgueras et al, 2009), and neuropathic pain after spinal cord lesion (Komori et al, 2004). More recently we demonstrated that MT5-MMP deficiency in the 5xFAD mouse model of AD remarkably ameliorated the outcome of the pathology affecting neocortical and hippocampal functions (Baranger et al, 2016b).…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, TNF-α levels were downregulated in the frontal cortex of TgMT5 −/− mice. Along this line, MT5-MMP deficiency has also been linked with deficient inflammatory response to TNF-α in the mouse PNS (Folgueras et al, 2009). Together, these data reinforce the idea that MT5-MMP may influence neuroinflammation in a cytokine- and region-dependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…N-cadherin mediated-mast cell-nerve interaction is regulated by matrix metallo-proteinase MMP24; Mmp-24 deficiency abrogates acute thermal hyperalgesia by altering neuron-mast cell synapses [73]. Mast cell mediators NGF and TNF-α influence neuronal growth, and both can lower the threshold of nociceptor firing through binding to TRK1-transforming tyrosine kinase protein (trkA) and TNF receptor, respectively [56,74, 75, 76].…”
Section: Mast Cell-neuron Synapse In Tissue Contribute To Pain Resmentioning
confidence: 99%
“…NGF and tumor necrosis factor-α (TNF- α) secreted by mast cells induce neuronal growth, and reduce subsequent neuronal firing threshold through binding with trkA and TNFR, respectively [55, 65, 66, 67]. Tryptase released by mast cells binds to proteinase-activated receptor 2 (PAR2) on neurons, and initiates a cascade involving TRPV1/4 activation via PLC and release of CGRP [72, 73]. CGRP in turn binds to a G-protein coupled receptor (CGRP-GPCR) on mast cells, and promotes histamine release [74, 75].…”
Section: Figurementioning
confidence: 99%
“…MMP-25 has also been linked with some pathological processes such as multiple sclerosis or cancer, but its biological role has remained largely unknown (11,12). In this work, and as part of our long-term studies aimed at generating mouse models of protease deficiency (5,(13)(14)(15)(16), we describe the generation of Mmp25-deficient mice and evaluate the biological function of MT6-MMP in innate immunity.…”
mentioning
confidence: 99%